Gulf of Mexico Hypoxia: Past, Present, and Future. (1st November 2019) - Rabalais, Nancy N.; Turner, R. Eugene
Abstract: One of the largest human‐caused areas of bottom‐water oxygen deficiency in the coastal ocean is on the northern Gulf of Mexico continental shelf adjacent to the Mississippi River, which discharges nitrogen and phosphorus loads into its surface waters. The beginnings of seasonal hypoxia (≤2 mg l −1 dissolved oxygen) in this area was in the 1950s with an acceleration in the worsening of severity during the 1970s. Currently, the bottom area of hypoxic areas can approach 23, 000 km 2, and the volume, 140 km 3 . Ecosystems, people, and economies are now at risk within the Mississippi River watershed and in the northern Gulf of Mexico. Strengthened nitrogen and phosphorus mitigation, altered agriculture practices, and reduction in carbon and nutrient footprints are key to the recovery of these systems. In this article, we review the past, present, and possible future conditions of the northern Gulf of Mexico and provide insight into possible management actions.